2017
DOI: 10.1016/j.juro.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Parents of Children Born with Atypical Genitalia 1 Year after Genitoplasty

Abstract: Overall the majority of parents were coping well 1 year after their child underwent genitoplasty. Level of decisional regret was related to having a bachelor's level of education, increased levels of illness uncertainty preoperatively and persistent illness uncertainty at 12 months after genitoplasty but was unrelated to postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…Peck and Feder (2017) have also urged consideration of how health care professionals in DSD teams may commit institutional evils-not out of conscious intentbut rather out of the failure to consider and challenge institutional norms which may reasonably be foreseen to bring about intolerable harms. Parents often chose interventions for their children in medical practice, when those interventions are made available to them (Ellens et al, 2017;Timmermans et al, 2018). Vulnerability to human rights abuse emerges at the intersection of familial and organizational socialities.…”
mentioning
confidence: 99%
“…Peck and Feder (2017) have also urged consideration of how health care professionals in DSD teams may commit institutional evils-not out of conscious intentbut rather out of the failure to consider and challenge institutional norms which may reasonably be foreseen to bring about intolerable harms. Parents often chose interventions for their children in medical practice, when those interventions are made available to them (Ellens et al, 2017;Timmermans et al, 2018). Vulnerability to human rights abuse emerges at the intersection of familial and organizational socialities.…”
mentioning
confidence: 99%
“…We reached to all corresponding authors and we received required data from Patanwala et al (2017) and Roley et al (2015). The remaining three publications (Ellens et al, 2017;Korenromp, Page-Christiaens, van den Bout, Mulder, & Visser, 2009;Rouhani et al, 2016) could not be included due to missing replies. As such, a total of 36 eligible publications were included in the narrative review and 24 samples from 21 publications in the meta-analysis (see Figure 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…Most patients (70.8%) considered the timing of their surgery correct (mean age at first surgery 2.1 years), while 3 patients said they were operated too late (9, 14, and 17 years) (30). Ellens et al reported that mental health problems and depressive symptoms in parents of children with DSD improved progressively 6 to 12 months after surgery (31).…”
Section: Surgical Aspectsmentioning
confidence: 99%